A COMPARATIVE STUDY OF THE LEGAL FRAMEWORKS FACILITATING INDIGENOUS LAND MANAGEMENT IN POSTCOLONIAL SOCIETIES: INDIGENOUS AUSTRALIA AND INDONESIAN ADAT LAW - Boag, Carly May (Faculty of Law, Universitas Brawijaya, 2016)
Indigenous Land Management (ILM) encompasses traditional philosophies and practices of Indigenous people with contemporary scientific techniques to help improve the management and conservation of ecosystems. An effective legal framework for ILM promotes environmental justice by â€œprotecting and fulfilling of human rights through legal empowerment of peopleâ€[1] through meaningful participation in environmental decision making from a regional to an international scale, acknowledgment of cultural differences and the equal distribution of environmental benefits[2]. Both Indonesia and Australia were colonised by European powers with devastating effects on the Indigenous people. Since the 1980â€™s there has been increasing international attention surrounding the lack of environmental justice accessible to Indigenous peoples around the world. Regional, national and international legal frameworks are in place in both Australia and Indonesia to promote globally recognised concepts of ILM, however there is a need for more cohesive and integrated approach at all levels of environmental governance. Although there are historical, cultural and economic differences between Australia and Indonesia as well as different legal ideologies, a comparative study of the different legal frameworks surrounding ILM will provide an insight into the benefits and limitations of divergent policy strategies and the best way forward for Indigenous peoples in the Asian-Pacific region.Â Â